2000
DOI: 10.1139/f00-222
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the stock-recruit relationship for Northeast Arctic cod using a bioenergetic index of reproductive potential

Abstract: Correlation and simulation analyses suggest that, for the Northeast Arctic (NA) cod stock, the total lipid energy (TLE (kJ)) contained in the livers of mature females is proportional to total egg production, making TLE a potential predictor of recruitment. Accordingly, the TLE of NA cod was estimated for a 51-year time period , using estimates of numbers at length derived from virtual population analysis, modelled values of proportion mature and weight at length, and observed values of the liver-condition inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…They are highly reduced compounds and are thus important fuels for oxidation. Lipid energy is transferred from algae to vertebrates via zooplankton and total lipid energy in kilojoules is a predictor of reproductive potential in fish stocks [14]. Marshall et al [15] found a highly significant linear relationship between total egg production in cod and total lipid energy.…”
Section: Lipid Nutritionmentioning
confidence: 99%
“…They are highly reduced compounds and are thus important fuels for oxidation. Lipid energy is transferred from algae to vertebrates via zooplankton and total lipid energy in kilojoules is a predictor of reproductive potential in fish stocks [14]. Marshall et al [15] found a highly significant linear relationship between total egg production in cod and total lipid energy.…”
Section: Lipid Nutritionmentioning
confidence: 99%
“…Many studies have described the effects of sea temperature on fish metabolism (Tyler and Colow, 1985;Solemdal, 1997;Martínez et al, 1999;Harvey, 2005;Stevens et al, 2006), growth rates (Rätz et al, 1999;Dutil et al, 2003), condition (Krohn et al, 1997), reproduction (Fedorov, 1971;Wootton, 1990;Jonsson and Jonsson, 2003;Privalikhin, 2003;Basilone et al, 2006;Coombs et al, 2006) or offspring survivorship (Lambert et al, 2003;O´Brien et al, 2003;Abdoli et al, 2005). Furthermore, water temperature also conditions fish population dynamics (Marshall et al, 2000;Armstrong et al, 2004;Yoneda et al, 2006) and distributions (Louge, 1996;Gordoa et al, 2000;Pájaro et al, 2005).…”
Section: Changes In Maturity Ogives In Response To Environmental Flucmentioning
confidence: 99%
“…2) were obtained from Marshall et al (2000) and were based on September-October acoustic surveys for 1973-1993 and on the frequency of capelin in cod stomach samples for 1959-1972. Marshall et al (2000 reported that the frequency of capelin in cod stomachs was most strongly correlated to acoustic estimates of capelin biomass the preceding autumn (n 5 24 yr, R 2 5 0.63).…”
Section: Methodsmentioning
confidence: 99%